1991
DOI: 10.3168/jds.s0022-0302(91)78272-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Immune Response in Peyer's Patch Cells Cultured with Bifidobacterium breve

Abstract: Bifidobacterium breve, included in fermented milk, was tested for adjuvanticity and mitogenicity using cells of mouse Peyer's patch, one of the gut-associated lymphoid tissues. Addition of B. breve enhanced antilipopolysaccharide antibody production in Peyer's patch cells and also anti-sheep red blood cell plaque-forming cells in Peyer's patch cells cultured with sheep red blood cells. Furthermore, addition of B. breve accelerated proliferation of Peyer's patch cells, particularly B cells. In BALB/c mice, enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 29 publications
1
47
0
2
Order By: Relevance
“…They can directly improve health status through stimulation of the activity of phagocytic cells as well as nonspecific humoral immunity mechanisms. The studies of other authors (9,16,18,26) showed that prebiotic supplementation, including inulin, enhances synthesis and secretory activity of IgA in the gastrointestinal tract. The present research included the analysis of the concentration of immunoglobulins class A, G, and M in piglet blood plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can directly improve health status through stimulation of the activity of phagocytic cells as well as nonspecific humoral immunity mechanisms. The studies of other authors (9,16,18,26) showed that prebiotic supplementation, including inulin, enhances synthesis and secretory activity of IgA in the gastrointestinal tract. The present research included the analysis of the concentration of immunoglobulins class A, G, and M in piglet blood plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, inulin contributes to the induction of immunoglobulin synthesis, especially IgA (16,26). Inulin fructooligosaccharides induce proliferation of beneficial microflora (Bifiobacterium and Lactobacteriaceae), which as probiotic bacteria improve animal rearing performance (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…It can specifically reach tumor tissue by circulation and grow in hypoxic solid tumors. Bifidobacterium is beneficial rather than nonpathogenic for its host, immunobiologic, 16,21 antiinfective, 22 and antiaging, 23,24 and observably inhibits the growth of tumors in mice. 25 Therefore, with Bifidobacterium as a vector for gene therapy, its inherent role as antitumor makes it more effective in inhibition of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…There are several advantages of selecting Bifidobacterium as gene delivery vector for cancer gene therapy: (1 ) Bifidobacterium is a domestic anaerobic bacterium in the human body that does not produce endotoxin and toxin; (2 ) Bifidobacterium increases immune response 16 and inhibits many tumor growth in vivo such as liver cancer, breast cancer, etc. ; 17 (3) Bifidobacterium can be killed easily by antibiotics or in oxygen environment in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In addition, combination treatment with TRAIL and chemotherapy showed a synergistic effect in human cancer cell lines and tumor xenograft models, even in drug-resistant cells and tumors. [12][13][14] Not only as probiotics but also as anaerobe, Bifidobacterium longum can be used as a useful host cell for heterologous protein production due to the following reasons: (1) protection of the intestinal mucosa and suppression of the permanent planting of detrimental gut microorganisms; 15,16 (2) induction of the releasing of endogenous mediator with immunological activity and enhancement of immunity of host 17 and (3) inhibition of tumor growth by suppressing cancer related genes, selective localization and proliferation within hypoxic tumors. [18][19][20][21][22] However, the fact that exogenous plasmids cannot replicate stably in Bifidobacterium limits the application of Bifidobacterium in cancer gene therapy.…”
Section: Introductionmentioning
confidence: 99%